Designing a Consumer Purchase Process Model in the Construction Industry - Soltani , Masoudreza; Haghshenaskashani, Farideh; Faez, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  The objective of this study is to explore the consumer purchase process in the construction industry.Methodology:  This qualitative research adopts the Glaserian grounded theory approach. Data were collected through semi-structured interviews with 19 experts in the construction industry and analyzed using open, selective, and theoretical coding with MAXQDA software. The study evaluated trustworthiness using Lincoln and Guba's criteria (credibility, transferability, dependability, and confirmability).Findings: The core category identified was the "consumer purchase process," influenced by causes such as persuasion, demographics, input stimuli, and perspectives. Correlated factors included marketing capabilities, personal factors, and real estate price fluctuation determinants. Contingencies such as individual factors, pre-purchase satisfaction, and company-related elements moderated the process. Mediating conditions, including purchase intention, product advantages, and financial factors, shaped outcomes like continuous improvement, advanced marketing, and innovation. Contextual elements, such as cultural, psychological, and social factors, were critical to the model's applicability.Conclusion: The study provides a comprehensive model integrating multi-dimensional interactions of consumer purchase processes in the construction industry. It highlights the need for future research to measure individual process stages, explore consumer behavior in other industries, and examine practical applications for improved marketing strategies and customer engagement.